Identification of the Role of miR-142-5p in Alzheimer’s Disease by Comparative Bioinformatics and Cellular Analysis - Song, Juhyun; Kim, Young-Kook (Frontiers in Molecular Neuroscience, 2017)
Alzheimer’s disease (AD) is the most common neurodegenerative disease characterized by the formation of amyloid beta (Aβ) or tau protein aggregates, the hallmark of cognitive decline. MicroRNAs (miRNAs) have emerged as critical factors in neurogenesis and synaptic functions in the central nervous system. Recent studies have reported alterations in miRNA expression in patients with AD. However, miRNAs associated with AD varied with patient groups or experimental models, suggesting the need for a comparative study to identify miRNAs commonly dysregulated in diverse AD models. Here, we investigated the miRNAs that show dysregulated expression in two different human AD groups and mouse and cellular AD models. After selection of commonly dysregulated miRNAs in these groups, we investigated the pathophysiological significance of miR-142-5p in SH-SY5Y neuronal cells. We found that miR-142-5p was increased upon treatment with Aβ peptide 1-42 (Aβ42). Inhibition of miR-142-5p rescued the Aβ42-mediated synaptic dysfunctions, as indicated by the expression of postsynaptic density protein 95 (PSD-95). Among genes with decreased expression in Aβ42-treated SH-SY5Y cells, the predicted miR-142-5p target genes were significantly related with neuronal function and synapse plasticity. These findings suggest that dysregulation in miR-142-5p expression contributes to the pathogenesis of AD by triggering synaptic dysfunction associated with Aβ42-mediated pathophysiology.